Preventing Medication Errors, The Essential Role of Pharmacists – A Comprehensive Review - JAIN MONAL YOGESH (International Journal of Multidisciplinary Research and Studies, 2023)
Medication errors cause significant risks to patient safety, contributing to morbidity, mortality, and increased healthcare costs globally. Pharmacists, play a key role in minimizing these errors through various interventions. This review examines the role of pharmacists in preventing medication errors across different stages of the medication process, including prescribing, dispensing, administration, and monitoring. Key pharmacist-led interventions such as medication reconciliation, patient and healthcare provider education, and the implementation of clinical guidelines are explored. The review also highlights the integration of technological solutions like computerized physician order entry (CPOE) and barcode medication administration (BCMA) systems, with pharmacists overseeing their effective use. Despite their expanding role, pharmacists face challenges such as high workloads, communication barriers, and systemic issues that limit their full potential in preventing errors. Future directions emphasize the need for policy reforms, inter-professional collaboration, and enhanced pharmacist involvement in direct patient care. By expanding the scope of pharmacists' responsibilities and integrating them further into healthcare teams, medication errors can be significantly reduced, improving patient outcomes and healthcare quality.